Determination of lead, cadmium, and arsenic concentrations in breast milk of women living in Misrata, Libya - Osama Serrar; Ali Sarrar; Ali Rafieda; Mohamed Daghman; Esraa M. Alhaj Abdullah; Noha M. Abo Oud (Scientific African, 2025)
Breast milk is a unique source of nutrition for infants and provides numerous short- and long-term benefits to mothers and infants. We aimed to detect Pb, Cd, and As levels in breast milk samples, investigate the effect of various factors on the concentrations of these metals in breast milk, and compare weekly intakes with the permissible levels specified by the World Health Organization (WHO) and Food and Agriculture Organization (FAO).Pb, Cd, and As levels were determined using microwave plasma atomic emission spectroscopy in 68 milk samples from healthy lactating women aged between 16 and 37. The samples were collected at approximately the second month postpartum from 28 different regions in Misrata; the participants were informed verbally about the purpose of the study, and they agreed to participate. All participants delivered through normal delivery between August 2016 and April 2017, and wet digestion procedures were applied for fat removal.The mean (standard deviation) of the Pb, Cd, and As concentrations in human milk were 21.24 (8.26) μg/L, 5.39 (14.80) μg/L, and 1.22 (1.53) μg/L, respectively. These results agree with the findings of other studies. In this study, 98.5, 68, and 46 % of milk samples contained Pb, Cd, and As, respectively, above the acceptable levels reported by WHO.The weekly Pb and Cd intakes were above the provisional level established for infants by the WHO and FAO in 20 and 22 samples, respectively. The mother’s age, place of residence, number of previous pregnancies, and exposure to passive smoke did not significantly affect the measured levels of heavy metals.The concentrations of Pb, Cd, and As in many samples were higher than the acceptable WHO levels, and the estimated heavy metal intakes of breastfed infants were higher than the provisional tolerable weekly intake in some cases.